Pengaruh Manajemen Talenta Terhadap Kinerja Karyawan pada Kafe Coffee Comunitas (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of talent management on employee performance at Kafe Coffee Comunitas. The research is grounded in the growing competitiveness of the food and beverage industry and the importance of human resource management in micro, small, and medium enterprises (MSMEs). The study investigates talent management practices, including recruitment, development, and retention of employees. A quantitative descriptive approach was employed using simple linear regression analysis. The sample consisted of 45 employees selected through a census method. The analysis revealed that talent management has a positive and significant effect on employee performance, with a significance value of 0.001 and a regression coefficient of 0.854. The coefficient of determination (R²) of 0.731 indicates that 73.1% of the variance in employee performance is explained by talent management. These findings highlight the strategic value of implementing effective talent management practices in MSMEs to enhance employee performance and organizational competitiveness.